2022
DOI: 10.3389/fimmu.2022.1006761
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen carrier M101 alleviates complement activation, which may be beneficial for donor organ preservation

Abstract: During organ transplantation, ischemia/reperfusion injury and pre-formed anti-HLA antibodies are the main cause of delayed graft function and recovery through the activation of the complement system. By supplying oxygen during transplantation, M101 is suspected to avoid complement activation, however, a direct effect exerted by M101 on this pathway is unknown. This was tested by using functional assays (lymphocytotoxic crossmatch test, C3d Luminex-based assay, 50% complement hemolysis [CH50], and 50% alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The immunological panel for SLE-associated biomarkers included: (i) the complement fractions C3, C4 (Cobas 500 ® , Roche Diagnostics GmBH, Germany) and 50 % concentration haemolytic (CH50; SpaPlus ® , The Binding Site, Birmingham, UK); (ii) IgG anti-double stranded (ds)DNA and anti-chromatin Abs (Bioplex ® , Biorad, Hercules, CA); (iii) IgG anti-extractable nuclear (ENA) Abs against sicca syndrome (SS)A 52 kDa, SSA 60 kDa, SSB, Smith (Sm), Sm-ribonucleoprotein (RNP), RNP A, and RNP 68 kDa antigens (Bioplex ® ); (iv) IgG anti-ribosomal Abs (Bioplex ® ); (v) IgG anti-C1q Abs (Quanta-lite ® , Werfen, Barcellona, Spain); and (vi) the spot urinary sCD163 (ELLA ® , Bio-techne, Minneapolis, MN) that was evaluated together with proteinuria and creatinuria (Cobas 500 ® ) in order to express sCD163 as a ratio to creatinuria, proteinuria, or not as well as the ratio of urine protein excretion to creatinine or PCR [ [22] , [23] , [24] , [25] , [26] ]. Cut-offs were fixed as recommended by the providers (C3 low <0.72 g/L; C4 low <0.11 g/L, CH50 low <31 %; anti-dsDNA Abs ≥10 international units [IU]/mL, anti-ENA/-Ribosomal/-Chromatin Abs ≥1.0 arbitrary units [AU]mL, and anti-C1q Abs ≥20 AU/mL) with the exception of the normalized urinary sCD163/creatinuria ratio as no consensus existed.…”
Section: Methodsmentioning
confidence: 99%
“…The immunological panel for SLE-associated biomarkers included: (i) the complement fractions C3, C4 (Cobas 500 ® , Roche Diagnostics GmBH, Germany) and 50 % concentration haemolytic (CH50; SpaPlus ® , The Binding Site, Birmingham, UK); (ii) IgG anti-double stranded (ds)DNA and anti-chromatin Abs (Bioplex ® , Biorad, Hercules, CA); (iii) IgG anti-extractable nuclear (ENA) Abs against sicca syndrome (SS)A 52 kDa, SSA 60 kDa, SSB, Smith (Sm), Sm-ribonucleoprotein (RNP), RNP A, and RNP 68 kDa antigens (Bioplex ® ); (iv) IgG anti-ribosomal Abs (Bioplex ® ); (v) IgG anti-C1q Abs (Quanta-lite ® , Werfen, Barcellona, Spain); and (vi) the spot urinary sCD163 (ELLA ® , Bio-techne, Minneapolis, MN) that was evaluated together with proteinuria and creatinuria (Cobas 500 ® ) in order to express sCD163 as a ratio to creatinuria, proteinuria, or not as well as the ratio of urine protein excretion to creatinine or PCR [ [22] , [23] , [24] , [25] , [26] ]. Cut-offs were fixed as recommended by the providers (C3 low <0.72 g/L; C4 low <0.11 g/L, CH50 low <31 %; anti-dsDNA Abs ≥10 international units [IU]/mL, anti-ENA/-Ribosomal/-Chromatin Abs ≥1.0 arbitrary units [AU]mL, and anti-C1q Abs ≥20 AU/mL) with the exception of the normalized urinary sCD163/creatinuria ratio as no consensus existed.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, alternative OCs have been developed as urgently awaited RBC replacement approach. In addition, those OCs usually exhibit beneficial features such as higher oxygen- and carbon dioxide-carrying capacity and a lower antigenicity ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…M101 was associated with higher ATP levels, indicating improved mitochondrial function, reduced oxidative stress levels, lower pro-inflammatory immune responses, and attenuated ischemia-reperfusion injuries ( 21 ). In addition, a recent study showed that M101 indirectly alleviates the complement activation by reducing ischemia-reperfusion injuries ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that M101 does not bind NO (nitric oxide), nor causes vasoconstriction, and has no immunogenicity, compared with other noncell-bound hemoglobin carriers (15–17). Studies in mice demonstrated an increase in the oxygenation of poorly vascularized tissues (18).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that M101 does not bind NO (nitric oxide), nor causes vasoconstriction, and has no immunogenicity, compared with other noncell-bound hemoglobin carriers (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%